2023
DOI: 10.3390/jcm12175747
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Carotid–Femoral Pulse Wave Velocity: A Systematic Review and Meta-Analysis

Iwona Jannasz,
Michal Pruc,
Mansur Rahnama-Hezavah
et al.

Abstract: COVID-19 is a complex multisystemic disease that can result in long-term complications and, in severe cases, death. This study investigated the effect of COVID-19 on carotid–femoral pulse wave velocity (cfPWV) as a measurement to evaluate its impact on arterial stiffness and might help predict COVID-19-related cardiovascular (CV) complications. PubMed, Web of Science, Embase, and the Cochrane Library were searched for relevant studies, and meta-analysis was performed. The study protocol was registered in PROSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Physiologically, capillary blood flow is continuous, also in diastole, since the energy delivered in systole is stored in the vascular system (referred to as "Windkessel-effect"). Interestingly, a recently performed clinical study used carotid-femoral pulse wave velocity as a measurement to predict COVID-19-related cardiovascular complications and found a marked increase in arterial stiffness and an increased carotid-femoral pulse wave velocity [54]. An increase in arterial stiffness is due to a structural loss of vascular elasticity or due to a high tone of conductance vessels to diminish the Windkessel function.…”
Section: The Interaction Of the Precapillary Cardiovascular Disturban...mentioning
confidence: 99%
“…Physiologically, capillary blood flow is continuous, also in diastole, since the energy delivered in systole is stored in the vascular system (referred to as "Windkessel-effect"). Interestingly, a recently performed clinical study used carotid-femoral pulse wave velocity as a measurement to predict COVID-19-related cardiovascular complications and found a marked increase in arterial stiffness and an increased carotid-femoral pulse wave velocity [54]. An increase in arterial stiffness is due to a structural loss of vascular elasticity or due to a high tone of conductance vessels to diminish the Windkessel function.…”
Section: The Interaction Of the Precapillary Cardiovascular Disturban...mentioning
confidence: 99%
“…As a result, COVID-19 may alter arterial stiffness [ 15 , 27 - 30 ]. Earlier studies have shown a significantly higher arterial stiffness index and pulse wave velocity (PWV) in COVID-19 non-survivors compared to survivors and the association between increased pulse pressure and in-hospital mortality [ 31 - 34 ]. Studies have revealed a high prevalence of cardiovascular diseases and risk factors in COVID-19 patients [ 35 - 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness is an important predictor of cardiovascular events and all-cause mortality [ 39 - 42 ]. Age, HTN, and other cardiovascular factors are associated with increased arterial stiffness, which, in combination with systemic inflammation, can worsen the course of COVID-19 [ 28 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%